Pertanggungjawaban Pelaku Penyelundupan Migran Lintas Negara Ditinjau Dari Hukum Internasional - Neladi Frisilia Lilipaly; Popi Tuhulele; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: As a country with many small islands bordering other countries, Indonesia has considerable potential for migrant smuggling practices. The smuggling of illegal immigrants is a type of global crime.Purposes of the Research: aims to identify and analyze international law governing the smuggling of transnational migrants as well as to identify and analyze the accountability of perpetrators who smuggle transnational migrants.Methods of the Research:  This legal research uses normative juridical research, case approach, statutory approach, and conceptual approach, primary and secondary legal materials, legal material procedures using primary legal materials which are then associated with secondary legal materials and processing and analysis of legal materials using qualitative descriptive analysis.Results of the Research: The results showed that the international legal arrangements that regulate migrant smuggling are the Palermo Convention (UN Convention / UNTOC) of 2000 concerning Transnational Crime (People Smuggling), the Migrant Workers Convention (International Labor Organization / ILO) of 1990, the Protocol for the Eradication of Smuggling involving People Smuggling 2000, and the perpetrators' accountability using the National Law or Indonesian Law, namely Law No. 6 of 2011 concerning Immigration.